2007
DOI: 10.1243/14644207jmda63
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic characteristics of a hybrid aluminium/composite drive shaft

Abstract: A static torque and power transmission capacities of a hybrid aluminium/composite drive shaft, fabricated by a wetted filament winding method, were investigated. Special mechanisms for static torsion and power transmission test setups were designed and fabricated. The following different fibre types were used: carbon, glass, one epoxy, and hardener. The static and dynamic characteristic of the hybrid aluminium/composite drive shaft with respect to the fibre types stacking sequences winding angle and number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Mutasher et al 6 compared the results of composite shaft torsion test with the results of the finite element analysis and found that the maximum torque coming from experiment was 4%-20% lower than the results from finite element analysis, which showed the reliability of finite element analysis result as well.…”
Section: Finite Element Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Mutasher et al 6 compared the results of composite shaft torsion test with the results of the finite element analysis and found that the maximum torque coming from experiment was 4%-20% lower than the results from finite element analysis, which showed the reliability of finite element analysis result as well.…”
Section: Finite Element Analysismentioning
confidence: 99%
“…They are calculated from these formulas Table 3 shows the mechanical properties of Tsai-Wu criteria of T300/5208. 6 The stress state of the lamina calculated by the program is described by the components s 1 , s 2 , and t 12 . s 1 is the laminate stress along the fiber direction, s 2 is the laminate stress transverse to the fiber direction, and t 12 is the laminate shear stress.…”
Section: Failure Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Esmaael and Taheri [3] investigated adhesively bonded joints, interference fit joints were examined by Lee and Lee [4] regarding finite-element simulation or by Croccolo et al [5] regarding additional adhesive bonding. Khalid et al [6] and Mutasher et al [7] reinforced metal pipes by wet filament winding. Figure 1 shows an example of a hybrid drive shaft.…”
Section: Introductionmentioning
confidence: 99%
“…Design of composite drive shafts for automotive applications [8,9] explained the comprehensive approach to the design of composite drive shafts and developed the preliminary design tools for quick analysis to meet the drive shaft performance requirements [10,11].…”
Section: Introductionmentioning
confidence: 99%